A Optimalisasi Kemampuan Penalaran Matematis melalui Metode Mind Mapping - Ammar Habib, Moch Naufal (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Increasingly rapid global developments raise complex problems that require effective and innovative solutions. Mathematical reasoning is the key to solving the problem. But on the other hand, learning in schools is still a lot of conventional learning and the development of the students’ mathematical reasoning skills is not optimal. The aim of this study was to explore the effectiveness of using mind map-based learning methods that were judged to be effective in developing mathematical reasoning skills. With a qualitative approach to literature studies, research results were obtained which showed that the method of mind mapping had a significant influence on the mathematical reasoning ability of the students. Library study sources are derived from previous research that had the same focus of study. Library reviews are used to analyze several studies related to the use of mind mapping-based learning methods and their influence on mathematical reasoning capabilities. This research is expected to provide an understanding of the importance of developing mathematical reasoning skills to form intelligent and critical generations